Analisis Sekuen Gen Tubulin-β Isotipe 1 Cacing Haemonchus contortus Isolat Resisten terhadap Benzimidazole pada Domba di Indonesia - Dyah Haryuningtyas; Wayan T. Artama (Jurnal AgroBiogen, 2008)
Benzimidazole (BZ)resistance to gastrointestinal nematodes in small ruminants(sheep and goat) has become a significant problem worldwide.Evidences of anthelmintic resistance to albendazole inIndonesia has been reported from some government ownedfarms in West Java, Central Java, and Yogyakarta. Previousstudy on the sheep parasite H. contortus had shown that theBZ resistance was related to selection for individuals in apopulation possesing a spesific β-tubulin isotype 1 gene. Thestudy is aimed to determine mutation on coding region ofcentral part of β-tubulin isotype 1 gene of H. contortus resistantstrain from Indonesia. Seven H. contortus worms wereisolated from four BZ resistant sheep from two governmentfarms (SPTD Trijaya, Kuningan, West Java, and UPTDPelayanan Kesehatan Hewan, Bantul, Yogyakarta), and froma BZ susceptible sheep from Cicurug, Sukabumi, West Java.DNA was extracted individually from female H. contortusworms. A fragment of 520 bp β-tubulin isotype 1 gene exon3, 4, 5 was amplified using the PCR technique and thensequenced. The results showed that a single mutationoccurred in codon 200 (from phenilalanine to tyrosine) hadcaused benzimidazole resistance in H. contortus from SPTDTrijaya, Kuningan, West Java. Mutation in β-tubulin isotype 1gene of H. contortus from UPTD Pelayanan KesehatanHewan, Yogyakarta, occurred in codon 198 (from glutamateto glycine), codon 201 (from cystein to stop codon), andcodon 202 (from isoleucyne to stop codon).